PENDUKUNG MATERI TAMAN PENDIDIKAN AL-QUR’AN MELALUI GAME EDUKASI UNTUK ANAK UMUR 6-10 TAHUN MENGGUNAKAN MACROMEDIA FLASH 8 - Kurniawan, Herman (Universitas Muhammadiyah Surakarta, 2011)
In the current era of education or education is an important foundation for promoting the young generation, but the learning process that saturate make young people lazy to learn, with advances in technology that now this game juaga made progress like playsation and computer games.?Computer games in a wide range of not only games that make kids lazy learning, educational game now appears to mengukti technological developments that will make teaching and learning process become more active and interesting.?One form of educational game is a safe material supporting the Education of Al-qur?an through educational game for children aged 6?10 years using macromedia falsh 8. This game has done the test, The test results can be concluded that the system created a program that has been going according to design purposes.?